Analysis of the Relationship Between Inflation, Unemployment, and Sectoral Development in Cirebon Regency: A Literature Review and Secondary Data Study (Islamic Economics) - Gama Pratama; Ali Ahmad Muhajir; Erni Erni; Eva Nurazizah; Muhammad Zidan Andriawan; Nur Aeni (Ecobankers : Journal of Economy and Banking, 2026)
The unemployment rate is an economic indicator that mutually influences regional development, while sectoral growth demonstrates the region's ability to optimally utilize its economic potential. Using secondary data and relevant theories, such as the Phillips curve explaining the relationship between inflation and unemployment, and sectoral growth theory, the research finds that changes in inflation and the unemployment rate in Cirebon affect the development of important sectors such as trade, industry, and agriculture. The analysis shows that increased inflation reduces people's ability to purchase goods and hinders real economic activity, while high unemployment causes productivity and growth in these sectors to decline. This research emphasizes the importance of interconnected policies in maintaining stable prices, creating jobs, and strengthening leading sectors to promote sustainable regional economic development.